Perlindungan Konsumen terhadap Pengguna Jasa Pengiriman Barang J&T Express Ungaran Timur - Maryatul Rifdiyah; Adi Suliantoro (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the implementation of consumer protection for users of J&T Express Ungaran Timur courier services based on Law Number 8 of 1999 on Consumer Protection. This study is empirical legal research using a juridicalsociological approach. Primary data were obtained through direct interviews with the branch manager, customer service staff, couriers and consumers of J&T Express Ungaran Timur. The results indicate that there are six main obstacles in fulfilling consumer rights: damaged goods, delayed delivery, lost goods, consumers' lack of understanding of claim procedures, the application of standard clauses potentially harmful to consumers and insufficient human resources during peak hours. J&T Express Ungaran Timur has undertaken differentiated efforts for each obstacle, corresponding to the consumer rights dimension affected as stipulated in Article 4 of the Consumer Protection Law. Nevertheless, implementation still requires further supervision to achieve optimal consumer protection.